Surface modification of cellulose using silane coupling agent - Thakur, Manju Kumari; Gupta, Raju Kumar; Thakur, Vijay Kumar (Elsevier, 2014)
Recently there has been a growing interest in substituting traditional synthetic polymers with natural polymers for different applications. However, natural polymers such as cellulose suffer from few drawbacks. To become viable potential alternatives of synthetic polymers, cellulosic polymers must have comparable physico-chemical properties to that of synthetic polymers. So in the present work, cellulose polymer has been modified by a series of mercerization and silane functionalization to optimize the reaction conditions. Structural, thermal and morphological characterization of the cellulose has been done using FTIR, TGA and SEM, techniques. Surface modified cellulose polymers were further subjected to evaluation of their properties like swelling and chemical resistance behavior
Keywords: Morphological and physico-chemical properties; Natural cellulose; Surface modification; Thermal